Power and the corporate mind - Zaleznik, Abraham; Kets de Vries, Manfred F. R. (Boston : Houghton Mifflin, 1975)
This book provides an understanding of the meaning of power and the nature of the corporate mind by offering well-documented and varied examples of executives and entrepreneurs, as well as psychoanalytic cases, to form its picture of the mind of the executive.
Includes index.
kjo 17/01/2019
Loans
Keywords: Executives; Leadership; Political psychology; Psychoanalysis; Organization and administration; Leadership; Psychoanalysis